Quality Comparison of Chicken Meat Treated with Origanum syriacum L. and Origanum vulgare L. Essential Oil Incorporated with Aloe vera Gel - Marwan A. Al-Hijazeen (Applied Sciences)
This comparison study assessed the antioxidant effectiveness of two oregano essential oils extracted from different plant species, namely, Origanum syriacum L. and Origanum vulgare subsp. hirtum, applied to 5% Aloe barbadensis miller gel using chicken meat. In addition, all treatment samples contained the same amount (5%) of Aloe vera gel. The results of the current research will help to distinguish between both oil types accurately. This study involved four different treatments: (1) Control, (2) 300 ppm of Origanum syriacum L. essential oil (OR-S), (3) 300 ppm of Origanum vulgare subsp. hirtum (OR-V), and (4) 14 ppm of butylated hydroxyanisole (BHA). Generally, natural antioxidants have many limitations when used for meat preservation compared to synthetic ones and should be combined with natural carriers. The treated meat patties were used to analyze lipid oxidation, color, total volatiles, and specific sensorial characteristics. Based on the current investigation, comparisons between treatments (OR-V, OR-S, and BHA) demonstrated that both of the combined oregano oils showed lower TBARS values. The control treatment showed the lowest preservation effect. Origanum syriacum L. (OR-S) and OR-V showed significant antioxidant effects compared to synthetic BHA. However, OR-S exhibited the strongest significant antioxidant effect and could be the best choice for industrial meat preservation.